Transmission of Al-Qur'an Learning in Saudi Arabia and Indonesia - Sri Widyastri; Abuddin Nata; Said Agil Husin Al Munawar; Suparto Suparto (International Journal of Islamic Thought and Humanities, 2022)
The purpose of this article is to unravel the root causes of the problem transmition of learning taḥfīẓ Al-Qur'ān through the sanad system at Iqra Global Academy for Qur’anic Studies in Kingdom of Saudi Arabiyah  and Mahad Imam Al-Bukhariy Wahdah Islamiyah Makassar. Both institutions have similarities in applying the study of classical books that are sanad, only Mahad Imam Al-Bukhariy does not apply the system of sanad taḥfīẓ Al-Qur'ān with other riwāyah such as riwāyah Qālūn 'an Nāfi'. Mahad Imam Al-Bukhariy Wahdah Islamiyah Makassar and Iqra Global Academy for Qur’anic Studies in Kingdom of Saudi Arabiyah has a paradigm that the function of sanad can maintain knowledge, authority and legitimacy. Both boards want to produce many sanad ḥuffāẓ who apply Islamic values ​​such as obedience to the rules of Allah, honesty, trust, discipline, fairness, sincerity, and responsibility. The teaching and learning process of tafīẓ Al-Qur'ān with the sanad system has a tendency to transmit original Islamic values ​​that have been passed down from generation to generation.